2017
DOI: 10.3233/jpd-160934
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrent Falls in People with Parkinson’s Disease and Proposal for a Predictive Tool

Abstract: Two predictive tools with moderate-to-high accuracy may identify people with PD at low, medium and high risk of falling recurrently within the next year. However, future studies to address external validation are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…falling in the previous 12 months = 6, freezing of gait in the past month = 3, gait speed <1.1 m per second = 2, with the sum giving a score between 0 and 11. The probability of falling in the next 6 months was then classified as low (0), moderate (2)(3)(4)(5)(6) or high (8)(9)(10)(11). this study may be due to the similar proportion of freezers among fallers and non-fallers in this study, compared to the development sample 3 and other external validation studies who had significantly more freezers among fallers.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…falling in the previous 12 months = 6, freezing of gait in the past month = 3, gait speed <1.1 m per second = 2, with the sum giving a score between 0 and 11. The probability of falling in the next 6 months was then classified as low (0), moderate (2)(3)(4)(5)(6) or high (8)(9)(10)(11). this study may be due to the similar proportion of freezers among fallers and non-fallers in this study, compared to the development sample 3 and other external validation studies who had significantly more freezers among fallers.…”
Section: Discussionmentioning
confidence: 71%
“…Falls are a frequent complication for people with Parkinson's disease (PD), with reported incidence rates for ≥1 fall ranging from 35% to 90% and many individuals presenting with multiple falls and falls‐related injuries 1 . Despite the identification of predictors of falls, including past falls; impaired balance, gait and cognition; freezing of gait (FOG) and fear of falling, 1–4 people with PD may present with different levels of fall risk and should be managed accordingly 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested an association between dyskinesia and falls 17 , whereas others failed to prove this. The same was true for wearing off, with some suggesting association 26 and others with inconclusive results 17 . In our sample, no difference was found in the MDS-UPDRS part IV, which assesses both wearing off and dyskinesia.…”
Section: Discussionmentioning
confidence: 76%
“…Although falling increases with disease severity, falls are even common in the early stages of the condition [ 10 ]. Anti-parkinsonian drugs are the main treatment to counter the symptoms that can cause PD patients to fall, while research into finding a cure continues.…”
Section: Introductionmentioning
confidence: 99%